Penggunaan abutment bersudut sebagai alternatif pada implan gigi premolar - Indra Tjiptadi, Reynaldo; Ariesanti, Yessy (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Success and longevity of dental implant treatments depend on treatment planning to prosthetic selection. Expected force applied should be taken into consideration as it may affect prosthetic rehabilitation. Case Report: A 26-year-old male presented with a complaint of missing 2 lower right teeth and desired a permanent dental prosthesis. Dental implant treatment was done on the patient, but the implants placed were not parallel to one another. The restoration was done using a straight abutment and an angled abutment. Conclusion: Angled abutment can be used as an option other than straight abutment but screw loosening should be expected in the future as the force applied to the implant is higher in angled abutment.